The Argumentative Scales in the Verses that Respond to Doubts of the Skeptics in Surat Al-Ma'idah (The Table Spread) and Al-An’am (The Cattle) - Almarri, Maryam; Elyaboudi, Khalid (Al-Adab Journal, 2024)
Arguments vary in their levels in terms of strength and weakness and their connection to the result they lead to. These arguments help in drawing conclusions because of the specific direction that they oblige the recipient to. This study aims to address the theory of the argumentative scales developed by Oswald Ducrot by highlighting the concept of the argumentative scales, its characteristics and laws, and investing the theory in analyzing Qur’anic texts in order to explore the hierarchy of arguments and their connection to each other, resulting in arguments that direct the recipient to the desired result, influence the recipient, and lead to persuasion. We will take the verses that respond to the doubts of the skeptics in Surat Al-Ma’idah and Al-An’am as a subject for the study.